The professional experiences of early career counselling psychologists in South Africa: a mixed method study - Haine, Phillipa Claire (Rhodes University, Faculty of Humanities, Department of Psychology)
Counselling psychologists represent a considerable proportion of psychologists in South Africa (SA), yet knowledge on the discipline's workforce is limited. In addition, professional lifespan issues have received inadequate attention, inclusive of the early career stage, identified as an exceptionally vulnerable segment of the professional lifespan. Undergirded by an interpretative phenomenology research paradigm, this mixed method sequential explanatory study, consisting of two distinct phases, aimed to explore the professional experiences of early career counselling psychologists (counselling ECPs) in SA, inclusive of employment trends, challenges and support needs. The quantitative phase ('First Phase') comprised of an online survey questionnaire (n = 512) to investigate the employment trends of counselling ECPs in SA. A qualitative phase ('Second Phase') followed, comprising of online semi-structured interviews with ten counselling ECPs. The rationale for this was that the preliminary quantitative data provided a broad understanding of the research problem, whereas the qualitative data sought to expand on the quantitative data by exploring the participants' experiences in depth. Moreover, the collection of quantitative data provided a strong justification and phenomenological orientation for the second, qualitative, phase. The data from the two research phases were combined within a joint discussion to ensure a level of methodological complementarity and a more holistic understanding of the data captured. Trends from the first, quantitative, phase demonstrated that counselling ECPs differed across various domains from more senior generations. In the second, qualitative, phase, Interpretative Phenomenological Analysis of the data revealed three Group Experiential Themes: i) Complexity of finding and securing work, ii) Navigating an array of personal, professional and systemic challenges, and iii) Support as self-acquired. Overall, the findings suggest that counselling ECPs in SA face a variety of challenges upon entering the workforce, enhanced support is thus needed for this new, more diverse cohort of practitioners. Actionable recommendations are offered at various levels.
Keywords: Counseling psychology -- South Africa; Career development; Counseling psychologists Training of -- South Africa; Mixed methods research; Interpretative phenomenological analysis